On the structure of the fundamental étale group of normal schemes - Mas Huamán, Ronald Jesús (2025)
The étale fundamental group is a central tool in algebraic geometry that generalizes the topological fundamental group to the context of schemes. In this article, we explore its behavior for normal schemes, highlighting its relationship to arithmetic and geometric invariants.